The relationship between breakfast habits and nutritional status of adolescent girls: A Cross-sectional study in Tasikmalaya - Dian Saraswati; Lilik Hidayanti; iseu siti aisyah (Department of Nutrition at the Health Polytechnic of Aceh, Ministry of Health, 2024)
Many adolescents in developing countries have a poor breakfast habit. Poor nutritional status is thought to occur due to poor breakfast habits. This study aimed to analyze the relationship between breakfast habits and nutritional status in female adolescents using the BAZ approach. This was an observational study that used a cross-sectional approach. Three hundred and thirty-six (366) participants were selected from seven State Junior High Schools in Tasikmalaya using the proportional random sampling method. This study was conducted between August and October 2023. Nutritional status was measured using the body mass index-age-Z score (BAZ), and breakfast habits were assessed using a structured questionnaire. Multiple linear regression modeling with a significance of p<0,05 was used for data analysis. From 366 participants, the average frequency of breakfast was 3,4 ± 2,5 times/weeks, with an average BAZ of -0,08 ± 1,2 SD. Breakfast habits were related to nutritional status using BAZ (p=0,031. This study concluded that the frequency of breakfast consumption in a week is negatively related to nutritional status based on BAZ in female adolescents. Therefore, they need to be encouraged to eat breakfast and determine the reasons why they skip breakfast.